Pengaruh Latihan Drill Shooting Bola Bergerak terhadap Ketepatan Shooting Futsal pada Siswa Ekstrakulikuler Futsal SMP Negeri 1 Sukoharjo - Januarda, Dimas; Indarto, Pungki (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to find out whether there is an effect of moving ball shooting drill training on futsal shooting accuracy among futsal extracurricular students at SMP Negeri 1 Sukoharjo. The method in this research is an experimental method with a one-group pre-test & post-test design. The sample in this research was 25 people taken using the purposive sampling method or objective sample. The analysis technique used is quantitative descriptive with statistics. The research results showed that the drill method affected students' shooting accuracy, as seen from the results of the paired sample t-test which showed a significance level of 0.000<0.05. In conclusion, there is an influence of moving ball shooting drill training on futsal shooting accuracy among futsal extracurricular students. Keyword: drill, Extracurricular, shooting accuracy